2019
DOI: 10.3390/molecules24040693
|View full text |Cite
|
Sign up to set email alerts
|

Disinfection by-Products and Ecotoxic Risk Associated with Hypochlorite Treatment of Tramadol

Abstract: In recent years, many studies have highlighted the consistent finding of tramadol (TRA) in the effluents from wastewater treatment plants (WTPs) and also in some rivers and lakes in both Europe and North America, suggesting that TRA is removed by no more than 36% by specific disinfection treatments. The extensive use of this drug has led to environmental pollution of both water and soil, up to its detection in growing plants. In order to expand the knowledge about TRA toxicity as well as the nature of its disi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 30 publications
5
17
0
Order By: Relevance
“…The available ecotoxicological data for this compound is very limited. However, our observation is consistent with the data recently published by the group of Romanucci et al (2019), who also did not observed any toxic effect of TRA towards V. fischeri at the concentration of 100 mg L −1 and documented the toxicity of TRA towards D. magna (EC 50, 24h = 88.5 mg L −1 ) and R. subcapitata (EC 50 = 87.1 mg L −1 ). Very low toxicity of TRA was also observed in the other studies (Αntonopoulou and Konstantinou 2016;Αntonopoulou et al, 2020).…”
Section: Resultssupporting
confidence: 93%
“…The available ecotoxicological data for this compound is very limited. However, our observation is consistent with the data recently published by the group of Romanucci et al (2019), who also did not observed any toxic effect of TRA towards V. fischeri at the concentration of 100 mg L −1 and documented the toxicity of TRA towards D. magna (EC 50, 24h = 88.5 mg L −1 ) and R. subcapitata (EC 50 = 87.1 mg L −1 ). Very low toxicity of TRA was also observed in the other studies (Αntonopoulou and Konstantinou 2016;Αntonopoulou et al, 2020).…”
Section: Resultssupporting
confidence: 93%
“…The OLM chlorination experiments were performed by mimicking the conditions of a typical WWTP, in which a 10 −5 M solution of the drug was treated for 10 min with 10% hypochlorite (OLM:hypochlorite molar ratio of 1:1; concn.) at room temperature [ 38 , 39 ]. Then, the tests are repeated at much higher concentrations of the contaminant (>10 −3 M), with a much lower ratio of OLM:oxidizing agent (1:5 or 1:6), so as to ensure the degradation of the studied contaminant and the possibility of isolating sufficient quantities of degradation byproducts for the subsequent structural identification.…”
Section: Resultsmentioning
confidence: 99%
“…The AMO chlorination experiments were performed by mimicking the conditions of a typical WWTP, in which a 10 −5 M solution of the drug was treated for 10 min with 10% hypochlorite (AMO/hypochlorite molar ratio of 1:1; concn.) at room temperature [45][46][47] for different pH values (Figures 1 and 2). The measurements of the AMO concentration as a function of time at the two different buffered pH values show how degradation was greater at pH = 7, with a percentage of about 80% after just 20-25 min of treatment.…”
Section: Chlorination Experimentsmentioning
confidence: 99%
“…The data reported in the literature for other emerging micropollutants generally observed longer reaction times, even in the order of hours. Oxidant concentrations even doubled that of the pollutant to ensure the complete mineralization of the latter, which was not infrequently after a double or triple treatment [44][45][46][47].…”
Section: Chlorination Experimentsmentioning
confidence: 99%